L’immaginazione conservatrice di Carl Schmitt - Monateri, Francesca (Aesthetica Preprint, 2023)
The aim of this paper is to analyse Schmittian aesthetics as an underrated theoretical aspect of Schmitt’s political thought. The scope of the paper is to show that Schmitt’s aesthetics should be considered the key factor to grasping the bulk of his theory. His theory – divided between formlessness and form, romanticism and Catholicism, politics and theology – can also be delineated as an alternative between nihilism and imagination. Therefore, this research concludes that imagination is not only a path for political reform, but it can also take on a politically conservative mission.